Transcription Dynamics and DNA Methylation Responses to Growth Modification - Kris A. Christensen; Étienne Collette; Danielle Perley; Dionne Sakhrani; Annette F. Muttray; Rosalind A. Leggatt; Carlo A. Biagi; Ben F. Koop; Robert H. Devlin (Marine Biotechnology, 2025)
To better understand how gene transcription is controlled under different physiological and environmental conditions, we assessed transcription and methylation responses in a vertebrate system (salmon) where growth can be manipulated in response to growth hormone transgenesis or under satiated, feed-deprived, and re-fed experimental conditions. In both transgenic and non-transgenic liver tissue, methylation of gene promoters was negatively associated with transcription at all measured times. However, the changes in promoter methylation among time-points did not generally correlate with changes in gene transcription among treatments. The results from this study suggest that only a subset of genes are readily responsive to changes in promoter methylation for a given environmental shift such as feed-deprivation or a physiological shift such as growth hormone transgenesis (i.e., genotype-by-environment interactions). The present study also reveals the complexity of how one tissue responds to alterations in internal changes in physiology (growth modification by growth hormone transgenesis; genotype), external environmental conditions (food availability; environment), and their interactions (genotype-by-environment effects).

Sexually Dimorphic Growth Stimulation in a Strain of Growth Hormone Transgenic Coho Salmon (Oncorhynchus kisutch) - Michelle T. T. Chan; Annette Muttray; Dionne Sakhrani; Krista Woodward; Jin-Hyoung Kim; Kris A. Christensen; Ben F. Koop; Robert H. Devlin (Marine Biotechnology, 2021)
Growth hormone (GH) transgenic fish often exhibit remarkable transformations in growth rate and other phenotypes relative to wild-type. The 5750A transgenic coho salmon strain exhibits strong sexually dimorphic growth, with females possessing growth stimulation at a level typical of that seen for both sexes in other strains harbouring the same gene construct (e.g. M77), while males display a modest level of growth stimulation. GH mRNA levels were significantly higher in females than in males of the 5750A strain but equivalent in the M77 strain, indicating sex and transgene insertion locus altered transgene expression. We found that acute estradiol treatments did not influence GH expression in either strain (5750A and M77) or the transgene promoter (metallothionein-B), suggesting that estradiol level was not a significant factor influencing transgene activity. The feminization of XX and XY fish of the 5750A and M77 strains generated all-female groups and resulted in equalized growth of the two genetic sexes, suggesting that the presence of the Y chromosome was not directly capable of influencing the GH transgene–mediated growth in a physiological female conditions. These data suggest that the difference in growth rate seen between the sexes in the 5750A strain arises from non-estradiol-mediated sex influences on gene regulation at the transgene locus. This study shows how genetic factors and transgene insertion sites can influence transgene expression with significant consequent effects on phenotype.

Effects of recombinant salmon type II growth hormone and bovine growth hormone on growth of coho salmon (Oncorhynchus kisutch) - Annette F. Muttray; Edward M. Donaldson; Robert H. Devlin (Fish Physiology and Biochemistry, 2019)

Physical, chemical, and microbial regimes in an anoxic fjord (Nitinat Lake) - Rich Pawlowicz; Susan A. Baldwin; Annette Muttray; Jana Schmidtova; Bernard Laval; Grant Lamont (Limnology and Oceanography, 2007)
New observations of physical, biological, and chemical parameters were obtained between July 2003 and February 2005 in Nitinat Lake, British Columbia, a permanently anoxic seawater fjord. These observations include continuous profiles of nitrate and bisulfide using a new instrument for in situ ultraviolet spectrophotometry. Anoxic seawaters in this 200‐m—deep basin can be found as shallow as 7 m. However, Nitinat Lake is surprisingly dynamic, with a deep‐water renewal time of only about 5 yr and significant spatial and temporal variability. Exchange with the ocean is limited by the size of the linking channel, and during low tides the outflow is subject to an hydraulic control. This nonlinearity causes a relatively large fortnightly cycle in water level and explains flooding events associated with heavy rainstorms. In addition, the restricted flow makes deep‐water renewal gradual so that anoxic conditions are preserved. Intermediate waters (5‐40 m in depth) are renewed alternately by oxygenation from surface mixing in winter and by upwelling of anoxic water and horizontal inflow of subducted ocean water in summer. The horizontal inflow results in a subsurface region of suboxic water in mid‐fjord during summer. No suboxic regime is evident at either the river end of Nitinat Lake (where oxygen and sulfide‐rich regions adjoin in a nitrate‐depleted water column) or at the ocean end of Nitinat Lake (where oxygen and nitrate‐rich regions sometimes overlap with sulfide‐rich regions). Maximum phytoplankton levels near the surface are high in both winter and summer. A second peak in biological activity appears near the anoxic boundary, possibly as a result of sulfur‐oxidizing bacteria. Sulfate‐reducing bacteria are also present in anoxic water in both seasons and just above the oxic/anoxic interface in winter and just above the suboxic/anoxic interface in summer.

Identification of DeltaN Isoform and Polyadenylation Site Choice Variants in Molluscan p63/p73-Like Homologues - Annette F. Muttray; Rachel L. Cox; Carol L. Reinisch; Susan A. Baldwin (Marine Biotechnology, 2007)

Porphyrin studies in TCDD-exposed workers - Detlev Jung; Johannes Konietzko; Gertraud Reill-Konietzko; Axel Muttray; Herbert -Josef Zimmermann-Hölz; Manfred Doss; Hans Beck; Lutz Edler; Annette Kopp-Schneider (Archives of Toxicology, 1994)